TGF-β-activated kinase-1: New insights into the mechanism of TGF-β signaling and kidney disease - Sung Il Kim; Mary E. Choi (The Korean Society of Nephrology, 2012)
Transforming growth factor-β (TGF-β) is a multifunctional cytokine that regulates a wide variety of cellular functions, including cell growth, cellular differentiation, apoptosis, and wound healing. TGF-β1, the prototype member of the TGF-β superfamily, is well established as a central mediator of renal fibrosis. In chronic kidney disease, dysregulation of expression and activation of TGF-β1 results in the relentless synthesis and accumulation of extracellular matrix proteins that lead to the development of glomerulosclerosis and tubulointerstitial fibrosis, and ultimately to end-stage renal disease. Therefore, specific targeting of the TGF-β signaling pathway is seemingly an attractive molecular therapeutic strategy in chronic kidney disease. Accumulating evidence demonstrates that the multifunctionality of TGF-β1 is connected with the complexity of its cell signaling networks. TGF-β1 signals through the interaction of type I and type II receptors to activate distinct intracellular pathways. Although the Smad signaling pathway is known as a canonical pathway induced by TGF-β1, and has been the focus of many previous reviews, importantly TGF-β1 also induces various Smad-independent signaling pathways. In this review, we describe evidence that supports current insights into the mechanism and function of TGF-β-activated kinase 1 (TAK1), which has emerged as a critical signaling molecule in TGF-β-induced Smad-independent signaling pathways. We also discuss the functional role of TAK1 in mediating the profibrotic effects of TGF-β1.